Host genetic variation in mucosal immunity pathways influences the upper airway microbiome. Issue 1 (December 2017) - Igartua, Catherine; Davenport, Emily; Gilad, Yoav; Nicolae, Dan; Pinto, Jayant; Ober, Carole
Abstract Background The degree to which host genetic variation can modulate microbial communities in humans remains an open question. Here, we performed a genetic mapping study of the microbiome in two accessible upper airway sites, the nasopharynx and the nasal vestibule, during two seasons in 144 adult members of a founder population of European decent. Results We estimated the relative abundances (RAs) of genus level bacteria from 16S rRNA gene sequences and examined associations with 148, 653 genetic variants (linkage disequilibrium [LD]r 2 < 0.5) selected from among all common variants discovered in genome sequences in this population. We identified 37 microbiome quantitative trait loci (mbQTLs) that showed evidence of association with the RAs of 22 genera (q < 0.05) and were enriched for genes in mucosal immunity pathways. The most significant association was between the RA ofDermacoccus (phylum Actinobacteria) and a variant 8 kb upstream ofTINCR (rs117042385;p = 1.61 × 10−8 ;q = 0.002), a long non-coding RNA that binds to peptidoglycan recognition protein 3 (PGLYRP3 ) mRNA, a gene encoding a known antimicrobial protein. A second association was between a missense variant inPGLYRP4 (rs3006458) and the RA of an unclassified genus of family Micrococcaceae (phylum Actinobacteria) (p = 5.10 × 10−7 ;q = 0.032). Conclusions Our findings provide evidence of host genetic influences on upper airway microbial composition in humans and implicate mucosal immunity genes in this relationship.